2019
DOI: 10.1128/jb.00028-19
|View full text |Cite
|
Sign up to set email alerts
|

The KupA and KupB Proteins of Lactococcus lactis IL1403 Are Novel c-di-AMP Receptor Proteins Responsible for Potassium Uptake

Abstract: Cyclic di-AMP (c-di-AMP) is a second messenger involved in diverse metabolic processes, including osmolyte uptake, cell wall homeostasis, and antibiotic and heat resistance. In Lactococcus lactis, a lactic acid bacterium which is used in the dairy industry and as a cell factory in biotechnological processes, the only reported interaction partners of c-di-AMP are the pyruvate carboxylase and BusR, the transcription regulator of the busAB operon for glycine betaine uptake. However, recent studies uncovered a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…Changes in external osmolarity trigger water fluxes across the membrane, which can lead to cell dehydration or swelling and, finally, collapse or burst when osmobalance mechanisms fail to respond properly (5). As a key component of these mechanisms, c-di-AMP directly targets transport systems for osmoactive and osmoprotective substances such as potassium ions and low-molecular-weight compatible solutes in many bacteria (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Changes in external osmolarity trigger water fluxes across the membrane, which can lead to cell dehydration or swelling and, finally, collapse or burst when osmobalance mechanisms fail to respond properly (5). As a key component of these mechanisms, c-di-AMP directly targets transport systems for osmoactive and osmoprotective substances such as potassium ions and low-molecular-weight compatible solutes in many bacteria (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Interestingly, experiments in Gram‐positive bacteria showed that the sensor kinase, KdpD is inhibited after cyclic‐di‐AMP (c‐di‐AMP) binding (Bai et al, ; Moscoso et al, ). Multiple recent reports lately have shown the impact of c‐di‐AMP in osmoregulation and its interaction with a TrkH effector protein (Zarrella et al, ; Pham and Turner, ; Quintana et al, ). However, c‐di‐AMP is not synthesized in Gammaproteobacteria (Commichau et al, ), such as S39006.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, considerable evidence has emerged that c-di-AMP plays a major role in osmotic regulation, primarily by positively regulating potassium export or negatively regulating potassium and osmolyte uptake (Rocha et al ., 2019, Quintana et al ., 2019, Kim et al ., 2015, Corrigan et al ., 2013, Moscoso et al ., 2015, Chin et al ., 2015, Huynh et al ., 2016, Schuster et al ., 2016, Pham & Turner, 2019, Pham et al ., 2018, Devaux et al ., 2018, Zarrella et al ., 2018, Gundlach et al ., 2017b, Gundlach et al ., 2017a, Gundlach et al ., 2017c, Gundlach et al ., 2019). However, individual c-di-AMP target proteins identified thus far are themselves not essential.…”
Section: Discussionmentioning
confidence: 99%
“…There is now considerable evidence that one such messenger, cyclic di-adenosine monophosphate (c-di-AMP) plays a significant role in osmoregulation in bacteria (Pham et al ., 2018, Pham & Turner, 2019, Quintana et al ., 2019, Zarrella et al ., 2018, Teh et al ., 2019, Fahmi et al ., 2019, Devaux et al ., 2018, Bai et al ., 2014, Zeden et al ., 2018, Corrigan et al ., 2011, Rocha et al ., 2019, Gundlach et al ., 2017b, Gundlach et al ., 2017a, Witte et al ., 2013, Whiteley et al ., 2015, Whiteley et al ., 2017). c-di-AMP binds to and negatively regulates a number of different potassium and osmolyte importers (Rocha et al ., 2019, Quintana et al ., 2019, Kim et al ., 2015, Corrigan et al ., 2013, Moscoso et al ., 2015, Chin et al ., 2015, Huynh et al ., 2016, Schuster et al ., 2016, Pham & Turner, 2019, Pham et al ., 2018, Devaux et al ., 2018, Zarrella et al ., 2018, Gundlach et al ., 2017b, Gundlach et al ., 2017a, Gundlach et al ., 2017c). c-di-AMP is essential for bacterial growth under standard growth conditions but it is also toxic at high levels in many Firmicutes, hence its cellular levels must be tightly regulated (Gundlach et al ., 2015b, Mehne et al ., 2013, Corrigan et al ., 2011, Corrigan et al ., 2015, Woodward et al ., 2010, Witte et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation